Language: A Catalyst for National Development (2013)
The author looks at strategies in the teaching and learning of Nigerian languages as second languages to foster peace and development in Nigeria. He observes that the Nigerian government has put some measures in place, just that some of these measures are poorly implemented and their aims defeated. The author makes some recommendations that would help to achieve a meaningful, peaceful co-existence, which is a catalyst for development.